Manufactured structural timber building materials and their durability. (30th August 2019) - Singh, Tripti; Page, Dave; Simpson, Ian
Highlights: Commonly used wood panels' bio-durability is highlighted in this research. The results showed untreated OSB and CLT were very susceptible to biodegradation. In comparison untreated LVL panels were less susceptible. Surface application of boron biocide prevented decay development. Research highlighted the need for further research to understand the extent of moisture ingress in wooden panels. Abstract: The use of sustainably grown trees and subsequent wood products in built environment contribute towards sustainable future. With proven improved performance in fire and seismic characteristic, the projected market potential for softwood Engineered Wood Products such as CLT (Cross Laminated Timber) and LVL (Laminated Veneer Lumber) for multi-story buildings are very positive. However, potential prolonged rain leakage or moisture exposure during construction and in-service could pose considerable concern for its durability and reputation. This research was conducted to assess the decay resistance of LVL, OSB (Oriented Strand Board) and CLT produced from radiata pine in an accelerated trial. This testing method is used in establishing the effectiveness of wood products in framing subject to intermittent wetting. The results showed untreated OSB and CLT were very susceptible to decay. In comparison, LVL was less susceptible. Testing conducted on CLT using surface application of boron preservative prevented decay. Further work is needed to understand the full extent of moisture ingress in wooden panels during construction and service of the multi-story buildings and improving the durability of panel products.